Amir Temur - Akbarova Saidaxon Akmalxon qizi, Parmonov Sharofiddin Shavkatovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article provides a comprehensive overview of the life and legacy of Amir Temur, also known as Timur or Tamerlane, who was a Turco-Mongol conqueror and the founder of the Timurid Empire in Central Asia in the 14th century.